Felicity Conditions of Speech Acts in Emma Watson's Social Media: Pragmatics Study - Ayu Yunita; Ervina CM Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The speaker has efficacy of speech acts referred to as the felicity condition. According to Austin (1962), when using speech acts, one must meet specific conditions related to the act being uttered. When one makes a promise to another person, for example, he or she must meet the condition that the hearer or promiser needs what is being promised, and the speaker or promiser has the intention to accomplish that need; thereby, the act of promising is valid and can be considered a felicitous condition. A felicity condition is defined as a state in which the speaker has words that meet the necessary conditions, such as proper context, customary existence, authority, and sincerity. This qualitative research deals with felicity conditions in Emma Watson’s social media, i.e., Twitter. The data source of this research is tweets related to felicity conditions. There are three types of felicity conditions found in this research, representatively preparatory conditions, propositional content conditions, sincerity conditions